PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI - Oktaviani, Oktaviani; Puspawati, Dewita (JURNAL LENTERA BISNIS, 2026)
The study decisively seeks to evaluate the impact of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on the financial outcomes of mining companies listed on the BEI for the 2023-2024 period. Furthermore, the study rigorously examines how profit management serves as a mediating factor in the correlation between the implementation of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) with financial performance. The research employed secondary data sourced from the annual financial statements of 32 mining companies, which were systematically analyzed using regression techniques with the support of SPSS software. The findings conclusively demonstrated that GCG significantly influenced profit management, while CSR showed no effect on profit management; GCG also had a crucial impact on financial performance, whereas CSR did not present a meaningful influence on financial outcomes, and profit management had a substantial effect on financial performance. Mediation regression analysis clearly established that profit management did not mediate the effect of GCG on financial performance, nor did it mediate the effect of CSR on financial performance.